Analisis Watak Dan Nilai-Nilai Pendidikan Karakter Pada Novel Ravendra Pernikahan Rahasia Siswa SMA Karya Winsari - Vevi Agustin; Kasmantoni; Dina Putri Juni Astuti (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to analyze the character traits and character education values in the novel Ravendra: Pernikahan Rahasia Siswa SMA by Winsari. The background of the study is based on the importance of literature as a reflection of social reality as well as an educational medium. The study uses a qualitative descriptive approach with a content analysis method, with objects in the form of relevant narrative excerpts and dialogues. Character analysis refers to M.H. Abrams' theory, while character education values refer to Thomas Lickona's theory. The results show that the author has succeeded in building character consistently, including dynamic characters (Ravendra, Kiara), static characters (Mama Elis, Syelin, Ken), and antagonists (Alena, Keisya). This novel also contains three dimensions of Lickona's character education, namely moral knowledge, moral feelings, and moral actions, which are reflected in the character's behavior such as empathy, responsibility, and integrity. Based on these findings, the novel Ravendra is suitable for use as a literary literacy teaching material in schools to instill character values in students. The recommendation of this study is the need for further studies on other Indonesian youth literature to enrich contextual character learning resources.